MODEL PENYELESAIAN SENGKETA PEMUTUSAN HUBUNGAN KERJA (PHK) DI INDONESIA - Jamillah Jamillah (Jurnal Ilmiah Penegakan Hukum, 2015)
One labour disputes according to Law 2 of 2004 on industrial relations disputesettlement in lieu of Law 22 of 1957 on the settlement of labor disputes is the terminationof employment. birth of Law 2 of 2004 was originally expected to bring fresh air to lawenforcement, because of the existence of this law passing guarantee the existence of a ruleof law, especially in the resolution of labor disputes through this legislation in theoryenough within 110 days of the trial has been completed to the industrial relations to thesupreme Court. but in practice is not in accordance with the theory, and the fact that thislabor dispute could take 5 to 6 years, this means that there is no difference with the oldrules